Protective effects of Dapagliflozin on the vulnerability of ventricular arrhythmia in rats with pulmonary artery hypertension induced by monocrotaline. Issue 2 (1st February 2022) - Qin, Tianyou; Kong, Bin; Dai, Chang; Xiao, Zheng; Fang, Jin; Shuai, Wei; Huang, He
ABSTRACT: Monocrotaline (MCT)-induced pulmonary artery hypertension (PAH) has been reported to cause right heart failure (RHF). Moreover, Right heart diseases have been determined to cause ventricular arrhythmia (VA). So we can conclude that MCT-induced PAH increases the incidence of VA. In addition, Previous studies have determined the benefits of Dapagliflozin (DA) on the cardiac system, but the responses of MCT-induced RHF to DA are not fully reported. So the present study sought to evaluate the effects of DA on the MCT-induced PAH. A dose intraperitoneal injection of MCT (60 mg/kg) was carried out to induce a rat model with PAH. DA (60 mg/l) was administered for 4 weeks following MCT injection. Echocardiography, body weight, blood pressure, blood glucose, electrophysiological study, and Western blot were performed. Four weeks after the MCT injection, MCT-treated rats decreased body weight, blood glucose and blood pressure. In addition, MCT caused the formation of PAH and RHF. Moreover, MCT-induced PAH rats increased the incidence of VA, prolonged action potential duration (APD), and shortened effective refractory period (ERP). Additionally, PAH rats significantly prevented the activated expressions of Ion channel proteins such as potassium channel (Kv1.5, Kv2.1, Kv4.2, Kv4.3) and L-type Ca channel (Cav1.2). As we expected, these changes above in PAH rats were reversed when DA was administered. Mechanistically, DA significantly reduced the levels of toll-like receptor (TLR4), the nuclear factor kappa B (NF-κB) in MCT-treated rats. In conclusion, these findings determine that DA reduces the vulnerability of VA in PAH rats through the TLR4/NF-κB signaling pathway.